Correlation of Blended Learning Aspects Based on Characteristic of Education and Training Participants based on the iPosyandu Midwife Application - Susanti, Ari Indra; Nuraini, Annisa; Fa’ni, Renidya Asyura Muttabi’ Deya; Chairiyah, Royani (Universitas Pendidikan Ganesha, 2024)
Education and Training (Diklat) with blended learning is training with learning carried out face to face directly and indirectly (synchronous and asynchronous). Asynchronous learning can use the iPosyandu application as a learning medium in professional training. However, success in the asynchronous learning process using the iPosyandu midwife application is related to the characteristics of the training participants. This research aims to analyze aspects of blended learning based on the characteristics of education and training (training) participants based on the iPosyandu Midwife Application. This research method used quasi-experimental with posttest design. Data were collected in this research by giving questionnaires about aspects of blended learning to 95 midwives with analysis of bivariate data with the Spearman statistical test using STATA version 15 software. This study showed no relationship between aspects of blended learning (pedagogical design, social design, ethnic design, different options) and the characteristics of training participants (age, education, occupation, period). work, last training) with a value of r=0.00-0.20; p-value>0.005. Thus, the iPosyandu Midwife application as mobile learning (mLearning) can contribute to learning for trainees using the Blended Learning method. iPosyandu midwife application can be used by trainees with various ages, education levels, occupations, and tenure, as well as training experience.